A Habit Strength-Based Explanation for Auditors' Use of Simple Cognitive Processes for Complex Tasks - Bonner, Sarah E.; Kadous, Kathryn; Majors, Tracie M. (The Accounting Review, 2022)
ABSTRACT We experimentally examine whether audit seniors' use of simple cognitive processes for a complex task is affected by the strength of habits that they developed as staff. A habit is a mental association between a behavior and a specific context. We propose that, for seniors with stronger habits to use simple processes, the typical audit room context automatically activates those processes, making it harder to select the processes that are more effective for a complex task. As predicted, we find that seniors with stronger habits identify fewer issues with a complex estimate than seniors with weaker habits when in the typical context. Seniors with stronger habits perform better in an alternative context that does not activate the simple processes, while those with weaker habits do not. Additional analyses validate that habit strength underlies our results and explore how the audit setting influences the development and enactment of habitual behaviors. JEL Classifications: G10; M40; M41; M42; D80; D91.